Analysis of the health product pipeline for poverty-related and neglected diseases using the Portfolio-to-Impact (P2I) modeling tool [version 1; peer review: 2 approved] - Alexander Gunn; Shashika Bandara; Nick Chapman; Gavin Yamey; Anna Doubell; Vipul Chowdhary; George Rugarabamu; Amelia Hynen (F1000Research, 2020)
Background: To estimate how much additional funding is needed for poverty-related and neglected disease (PRND) product development and to target new resources effectively, policymakers need updated information on the development pipeline and estimated costs to fill pipeline gaps. Methods: We previously conducted a pipeline review to identify candidates for 35 neglected diseases as of August 31, 2017 (“2017 pipeline”). We used the Portfolio-to-Impact (P2I) tool to estimate costs to move these candidates through the pipeline, likely launches, and additional costs to develop “missing products.” We repeated this analysis, reviewing the pipeline to August 31, 2019 to get a time trend. We made a direct comparison based on the same 35 diseases (“2019 direct comparison pipeline”), then a comparison based on an expanded list of 45 diseases (“2019 complete pipeline”). Results: In the 2017 pipeline, 538 product candidates met inclusion criteria for input into the model; it would cost $16.3 billion (B) to move these through the pipeline, yielding 128 launches. In the 2019 direct comparison pipeline, we identified 690 candidates, an increase of 152 candidates from 2017; the largest increase was for Ebola.  The direct comparison 2019 pipeline yields 196 launches, costing $19.9B. In the 2019 complete pipeline, there were 754 candidates, an increase of 216 candidates from 2017, of which 152 reflected pipeline changes and 64 reflected changes in scope. The complete pipeline 2019 yields 207 launches, costing $21.0B. There would still be 16 “missing products” based on the complete 2019 pipeline; it would cost $5.5B-$14.2B (depending on product complexity) to develop these products. Conclusion: The PRNDs product development pipeline has grown by over a quarter in two years. The number of expected new product launches based on the 2019 pipeline increased by half compared to 2017; the cost of advancing the pipeline increased by a quarter.